Tailoring the Self-Assembly of Steviol Glycoside Nanocarriers with Steroidal Amphiphiles - Kämäräinen, Tero; Kadota, Kazunori; Arima-Osonoi, Hiroshi; Uchiyama, Hiromasa; Tozuka, Yuichi (ACS Biomaterials Science and Engineering, 2023)
Bile salts are biosurfactants that can induce structure transformations in supramolecular nanoassemblies with conventional surfactants owing to their unique, planar amphiphilic character and the rigidity of their hydrophobic steroid skeleton. However, structural information about the association of bile salts and amphiphilic glycosides is lacking. In this work, we investigated the micelle structure of two anionic di- and trihydroxy bile salts [sodium deoxycholate (SDC) and sodium cholate (SC)] and a conventional anionic surfactant [sodium dodecyl sulfate (SDS)] in mixtures with a nonionic steviol glycoside [α-glucosyl stevia (Stevia-G)] and studied their potential as a nanocarrier system for two poorly water-soluble drugs (clotrimazole and ketoconazole). Decreased critical micelle concentrations determined from surface tension measurements demonstrate synergistic interactions between Stevia-G and SDS/SDC/SC in a decreasing order. Small-angle X-ray and neutron scattering, interpreted by a core-shell ellipsoid model, indicate that SDS and bile salts act differently on the mixed micelle structure. Compared with SDS/Stevia-G, bile salt/Stevia-G had a core-shell structure more similar to that of pure Stevia-G micelles. SDC and SDS had an increasing and decreasing influence, respectively, on the available molecular surface area in mixtures with Stevia-G on the micelle core but a similar influence on the micelle shell solvation number relative to that of their pure micellar structures. The number of bile salt hydroxyl groups was influential in determining the micelle stoichiometry: an increasing number of hydroxyl groups corresponded to decreasing bile salt aggregation numbers and a smaller hydrophobic micellar core. The core volume was the most important structural factor in explaining the drug solubilization capacity of the nanocarrier systems. Therefore, bile salt-steviol glycoside mixed micellar assemblies exhibit structure control mechanisms allowing the fine-tuning of their interior hydrophobic domains important for nanocarrier applications toward solubilization of poorly water-soluble drugs.
Created from Fastlane, Scopus look-up
Keywords: bile salt; biosurfactant; drug solubilization; mixed micelle; small-angle scattering; stevia